Analysis of The Potential Recreational Sports Tourism Via Ferrata In Taman Rancah Pemalang Regency (Nutrizione: Nutrition Research And Development Journal, 2022)
Recreational sports tourism via ferrata is a new and only sport tourism in Pemalang. The focus of the research is on the analysis of the potential for recreational sports tourism via ferrata in terms of human resources (HR), facilities and infrastructure, as well as obstacles that hinder the development of recreational sports tourism via ferrata in Taman Rancah, Pemalang district. The research used descriptive qualitative method. The object of research is recreational sports tourism via ferrata in Taman Rancah, Pemalang district. Research subjects: Head of tourism dinporapar Pemalang regency, chief manager, visitors, and the surrounding community. Data collection techniques using Observation, Interview, Documentation. The results of the study show that recreational sports tourism via ferrata in Taman Rancah Pemalang Regency has the potential to be seen from human resources (HR) that are already good, the facilities and infrastructure are quite complete and in a condition suitable for use. Some of the obstacles that hinder development include: capital, marketing, and have not established cooperation with other stakeholders. Suggestions of researchers, managers of recreational sports tourism via ferrata in Taman Rancah Pemalang Regency must always develop and improve the quality of both human resources and existing facilities and infrastructure and immediately find solutions to overcome existing obstacles.